Systematic review and meta-analysis of the association between complement factor H I62V polymorphism and risk of polypoidal choroidal vasculopathy in Asian populations. - Zhao-Yang Wang; Keke Zhao; Jingwei Zheng; Brian Rossmiller; Cristhian Ildefonso; Manas Biswal; Pei-quan Zhao (PLoS ONE)
Purpose To investigate whether the polymorphism rs800292 (184G>A, I62V) in the complement factor H gene is associated with polypoidal choroidal vasculopathy (PCV) and the genetic difference between PCV and neovascular age-related macular degeneration (nAMD), in Asian populations. Methods A comprehensive literature search was performed in PubMed, Medline, Web of Science, and reference lists. A system review and meta-analysis of the association between I62V and PCV and/or nAMD were performed from 8 studies involving 5,062 subjects. The following data from individual studies were extracted and analyzed: 1) comparison of I62V polymorphisms between PCV and controls; 2) comparison of I62V polymorphisms between PCV and nAMD. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using fixed-effects models. The Q-statistic test was used to assess heterogeneity, and Egger's test was used to evaluate publication bias. Sensitivity analysis and cumulative meta-analysis were also performed. Results The I62V polymorphism showed a significant summary OR1 for genotype GA+GG versus homozygous genotype AA was 3.18 (95% CI, 2.51-4.04, P<0.00001), the OR2 of heterozygous genotype GA versus AA was 2.29 (95% CI: 1.79-2.94, P<0.00001), the OR3 of homozygous genotype GG versus AA was 4.42 (95% CI: 3.45-5.67, P<0.00001), and the OR4 of allele G versus A was 2.04 (95% CI: 1.85-2.26, P<0.00001). Sensitivity analysis indicated the robustness of our findings, and evidence of publication bias was not observed in our meta-analysis. Cumulative meta-analysis revealed that the summary ORs were stable. There was no significant difference in every genetic model between PCV and nAMD (n = 5, OR1 = 0.92, OR2 = 0.96, OR3 = 0.90, OR4 = 0.94). Conclusions Our analysis provides evidence that the I62V polymorphism is associated with an increased risk of PCV. The variant of I62V could be a promising genetic biomarker of PCV in Asian populations.